Prevalence of mental illness, substance use disorder, and dual diagnosis among adults in custody - Darcy J. Coulter; Lindsay A. Pearce; Matthew Legge; Jesse T. Young; David B. Preen; Ed Heffernan; Jocelyn Jones; Stuart A. Kinner (Population Health Metrics)
Abstract Background The prevalence of mental illness, substance use disorders, and their dual diagnosis is disproportionately high among people in prisons compared to the community. Accurate prevalence estimates are required to inform resourcing of prison health services and reduce the risk of harm to people experiencing these conditions. Existing estimates, where available, often rely on only one data source. Method We used three data sources – self-reported history of diagnoses, in-prison medical records, and administrative data to estimate the prevalence of mental illness, substance use disorder, and dual diagnosis among two large cohorts of non-Indigenous and Aboriginal and Torres Strait Islander people in Australian prisons. We calculated population-weighted proportions of the samples with each condition. Inter-rater reliability metrics inform data source agreement. Results The prevalence of mental illness only, substance use disorder only, and dual diagnosis was 17.0% (95%CI 12.0–24.5), 14.8% (95%CI 9.6–18.1), and 44.2% (95%CI 33.2–54.7), respectively, for incarcerated, non-Indigenous adults. For incarcerated Aboriginal and Torres Strait Islander adults, our corresponding estimates were 7.0% (95%CI 4.3–11.5), 26.8% (95%CI 18.9–33.5), and 40.9% (95%CI 30.1–48.2). These estimates differed significantly from those derived from singular data sources. Individual data sources’ agreement was weakest for substance use disorder diagnoses and strongest for dual diagnoses. Conclusions Individual data sources likely have high specificity and low sensitivity, thus under-ascertaining diagnoses. We recommend using multiple data sources to estimate prevalence to ensure adequate ascertainment of these conditions among people in prison and to ensure in-prison and transitional health services are appropriately resourced.